EFL Student's Reading Habits in The Digital Era - Nurfaizah, Dayang; Erniyati, Yelni; Pranata, Ogi Danika (Universitas Islam Negeri Raden Intan Lampung, 2024)
In this modern era, easy access to digital media and the internet is a big challenge in reading habits. This research investigates internet usage patterns and reading habits among English students in contemporary educational settings. Drawing on data from a questionnaire survey administered to 53 students at an Islamic college in Jambi, Indonesia, the study explores students' online activities, reading preferences, and perceptions of digital reading materials. The findings show a significant reliance on the Internet for academic and leisure activities, with online news being the main driver of students' reading interest. Despite concerns about content relevance and readability, digital reading materials, especially e-books, and online platforms, have the potential to foster reading engagement and literacy skills. The study also highlights the diverse nature of students' online activities, emphasizing the need for tailored approaches to promote reading habits in the digital age. By adopting innovative teaching methods and utilizing digital resources, educators can create immersive reading experiences that help students navigate and critically evaluate digital information effectively. This research contributes valuable insights into the evolving landscape of reading preferences and the role of technology in shaping literacy practices, informing evidence-based strategies for promoting reading engagement and lifelong learning in educational contexts.